Design and analysis of medium scale water production using solar parabolic trough collector with turbulator baffles - Abdulhamed, Ali Jaber (2018)
Source of clean drinkable water is a big problem in the world. Water purification process consume the fuel which extremely effect on environment, economy, and human health. Solar parabolic trough collector (PTC) was built to meet the requirement of drinking water for the village members in a desert areas without relying on fossil fuel. The PTC powered by solar energy is the most favorable compared to flat plate because higher temperature is obtained. The design, fabrication, and performance of a stainless steel solar-powered parabolic trough collector (PTC) with a 90° rim angle and 3 m×1.314 m aperture area as a hot water generating system were investigated in this research. The gravity-load- and thermal-expansion-induced deformation of the receiver tube (δR ) was also investigated. . Comparing such deformation with the width of the solar image in the focal plane (w) revealed a maximum deformation of 1.43 mm in the mid length of the receiver tube that was within acceptable limits. The deformation of the receiver tube is an important new test to assess the thermal performance of PTC. The performance of PTC was assessed based on the ASHRAE Standard 93. In this work, thermal and thermodynamic performance of a receiver tube for a (PTC), heat transfer enhancement and pressure loss penalty for receiver exchangers equipped with baffles turbulator are experimentally and numerically investigated in a relatively low Reynolds number flow. Artificial obstructions on the underside of receiver tubes can increase the heat transfer coefficient between the receiver tubes (heat exchanger, HX) of (PTCs) and water as a working fluid. In this study, a numerically and experimentally tested the behavior of laminar mixed convective heat transfer in HX tube installed with baffles. These baffles are 20-rings that are connected together axially and connected radially to the inner tube surface. Using ANSYS FLUENT version 15.0, a performed computation fluid dynamics (CFD) modeling to achieve heat transfer enhancement in HX tubes equipped with turbulator baffles under laminar flow conditions were carried out. Moreover, the effects of pitch ratio (Pitch /Diameter) (P/D) = 3, 6, and 10 and Reynolds number Re ≤ 480 were recorded. The novel application of the rings that are connected axially together and radially to the inner tube surface contributes to the long-term storage of thermal energy and promotes heat transfer via conduction from the tube surface to the center line of the water flow within a short period. In the study, the baffles generated a vortex to increase the Nusselt number (Nu) inside the HX. To simulate heat flux, a calculated the constant wall heat flux of the receiver tube using an electric heater. Results indicated that using 20 rings as baffles produces maximum heat transfer at Nu< 30 instead of plain tubes improves heat transfer by up to 75%. As P/D decreased and Re increased, the heat transfer rate, thermal enhancement factor (TEF) increased. The friction factor, TEF and the Nusselt number for the receiver tube with baffles were compared with those of plain tube without baffles under similar flow conditions to determine the heat transfer enhancement. The correlations for the Nusselt number, friction factor, and TEF were developed a PTC receiver tube equipped with artificial baffles. The developed system is capable of delivery 226 L/day water at ≥ 50°C.